Utilizing a Standardized Handoff Initiative Incorporating Both Medical Clearance Postoperative Recommendations and Orthopaedic-Specific Context to Improve Information Transfer. (July 2022) - Meneses, Michelle; Muthusamy, Nishanth; Vetter, Mary Jo; Schwarzkopf, Ran
Abstract : Patients undergoing total joint arthroplasty (TJA) with multiple comorbidities require medical clearance recommendations from their primary care provider, which if not adhered to can lead to adverse postoperative complications. In this quality improvement initiative, we explore the impact of a standardized handoff process incorporating medical clearance postoperative recommendations and orthopaedic-specific context on information transfer in TJA. A systematic review of quantitative and qualitative studies from 2014 to 2019 was completed to draw a conclusion about the best practice methods for the development of a standardized handoff process. Prior to implementation, evidence was reviewed to inform activities such as baseline chart audits, attainment of stakeholder input regarding handoff, exploration of wound closure equipment utilization, and standardization of a structured "smart phase" that incorporates medical clearance recommendations and orthopaedic-specific context information. After provider education was completed and the new handoff approach initiated, data were collected to compare postintervention outcomes such as transfer of information and wound kit distribution cost analysis. At baseline, 42% of patients had medical clearance postoperative recommendations handed off when they were provided. At completion, the new handoff smart phrase was used 97% for the first handoff and 100% for the second handoff. Medical clearance postoperative recommendations were captured in the electronic health record 83% of the time when they were provided. When the new smart phrases were utilized, wound closure, precautions, and postoperative void status were always handed off. Once wound closure technique was specified, bedside nurses were able to provide the appropriate wound closure removal equipment at discharge, projecting cost savings of 0.69 per case (∼234 cases per month). The use of a standardized handoff smart phrase that includes specialty specific context and postoperative medical management requirements successfully improved the information transfer between providers in a large academic orthopaedic medical center.